P-196 Assessing human embryo implantation competence through analysis of extracellular vesicles and their contents. (30th June 2022) - Pavani, K.C; Tilleman, K; Stoop, D; Gadella, B; Hendrix, A; Van Soom, A
Abstract: Study question: Could extracellular vesicles (EVs) derived from spent media serve as a non-invasive quality marker for embryo implantation and pregnancy? Summary answer: EVs isolated from spent media derived from human blastocysts that either did or didn't establish a pregnancy after transfer differ in size, concentration, miRNA expression. What is known already: EVs are important for communication from one cell to another, influencing the translation of genes to proteins. They play a regulating role during biological processes, including pregnancy. We hypothesized that EVs released by a high-quality human embryo, which has the potential to create a pregnancy after the transfer, differ from EVs released by poor quality non-implanting embryos. Study design, size, duration: Patients scheduled for a fresh single blastoycst transfer in IVF/ICSI cycles using own gametes consented to sampling of spent culture media (n = 102). Spent media from the transferred blastocyst (25 μl) were collected from implanted (hCG+/ET) (n = 45) and non-implanted (hCG-/ET) (n = 51). Spent media from degenerated embryos (n = 21) were collected from 6 patients. Media samples were pooled randomly into three replicates for each group (implanted (I), non-implanted (NI), degenerated (DG)). Participants/materials, setting, methods: Extracellular vesicles were isolated by qEV single size exclusion column(SEC):a maximum of 200 µl of implanted or non-implanted or degenerated spent media was loaded onto the qEV SEC. Identification and characterization of EVs was performed by nanoparticle tracking analysis, transmission electron microscopy, and western blotting (CD9, CD63). Next, EV-RNA isolation was performed on these three groups (three replicates from each group) by Norgen Biotek Exosomal RNA Purification Kit, followed by RT-qPCR, and further data analysis. Main results and the role of chance: Extracellular vesicles isolated from the SEC column are referred to as I-EVs, NI –EVs, and DG-EVs (implanted, non-implanted, and degenerated, respectively). Western blot confirmed the presence of EV-specific markers (CD63, CD9) in all EV samples (I-EVs, NI-EVs, and DG-EVs). By NTA, a higher particle concentration was observed in I-EVs (2.69±1.9 × 1010 particles/mL) compared to NI-EVs (6.13±0.2 × 1010 particles/mL) (p < 0.05), whereas DG-EVs particle concentration (4.97±0. 2 × 109 particles/mL) was significantly (P < 0.01). I-EVs were also characterized by a larger particle size with an average mean diameter of 180.3±5.4 nm, whereas NI-EVs displayed a smaller particle size with a mean diameter of 141.5±2.5 nm (p < 0.05). TEM confirmed the presence of larger-sized vesicles in I-EVs (≥ 200 nm) compared with NI and DG samples. During earlier work in EVs from bovine blastocysts we found miR-378a-3p to be typically present in blastocyst EVs, with a prominent role in the hatching process of the blastocyst. Here, we compared miR-378a-3p expression levels by RT-qPCR in I-EVs vs. NI-EVs vs DG-EVs. Higher expression of miR-378a-3p was identified in NI-EVs and I-EVs, compared to DG-EVs (log2fc= 30.10, log2fc = 8.94 p < 0.001 respectively), but was not correlated with implantation rate. Limitations, reasons for caution: Currently, the methodology is unable to study EVs from a single droplet of spent media, hence pooling of the samples is necessary. As a consequence, data on EV-miRNA from individual blastocyst is lost. Wider implications of the findings: Our data demonstrated that EVs and their cargo (miRNAs) have potential to be used as a non-invasive method to predict embryo implantation:miR-378a-3p has been associated with hatching in bovine embryos, but was not related with human implantion. Other embryo-derived miRNAs may be tested as a possible biomarker for human pregnancy. Trial registration number: EC 2018/0266 – B670201835577